(untitled) (Contemporary Journal of Social Science Review, 2026)
This study examines the sociopolitical effects of English as the dominant language in Pakistan’s state institutions through a corpus-assisted critical discourse analysis across education, law, and banking. It investigates how English functions as a carrier of ideology, authority, and professional communication, and how its dominance influences access, participation, and institutional power in a multilingual society. This study asks how English, as the language of state institutions, shapes sociopolitical challenges in Pakistan. A mixed-methods corpus-based design combines quantitative analysis (lexical frequency, collocations, and variation) with qualitative discourse analysis of institutional texts and stakeholder perspectives, using data from policy documents and sectoral communication. Findings show clear functional variation across domains: in education, English is tied to academic achievement and global legitimacy; in law, it serves as a formal regulatory and authoritative medium; and in banking, it operates as a technical and efficiency-oriented language. Despite these differences, English maintains a consistent hegemonic position across all sectors. Urdu and regional languages are largely confined to explanatory and interactional roles, while English dominates formal institutional communication, creating a hierarchical bilingual structure that privileges English proficiency and limits equitable access. Statistical analysis confirms significant cross-sectoral differences in lexical and discourse patterns, reinforcing functional language stratification. The study argues that English hegemony is contextually realized as ideological, regulatory, and functional dominance rather than a uniform phenomenon. It concludes that English in Pakistan functions as a sociopolitically loaded resource that reinforces institutional authority and social inequality, and recommends a more inclusive multilingual policy to balance global demands with local linguistic realities.